Permanent creation, Ecosophy and Eco-Artivism: An interdisciplinary journey with Robert Filliou, Félix Guattari and Transnational Temps - López Martín, Elena; Morgado Aguirre, Borja (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The aim of this article is to explore the convergence between Félix Guattari's ecosophical perspective, Robert Filliou's theories, and the eco-artivist approaches of Transnational Temps, fostering interdisciplinary dialogue in the context of new telecommunications technologies. Through critical analysis of their works and theories, and supported by original and unpublished interviews with members of Transnational Temps, this study shows how the intersection of these ideas promotes an interconnected future where everyday activism through art and creativity offers a vision of a more conscious and harmonious alternative society.